Constructing Masculinity Through Anti-Establishment Discourse in The Joe Rogan Experience: A Critical Discourse Analysis: A. Introduction - Jumharia Djamereng (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Podcasts are increasingly popular alternative media platforms and have transformed modern public discourse through their informal, lengthy, and ideologically driven conversations. In this context, masculinity has become a hot topic, particularly with respect to institutional authority, authenticity, and freedom of expression. This paper investigates the construction of masculinity in anti-establishment discourse in the Joe Rogan Experience with Mark Zuckerberg. The study adopts a qualitative research design and uses the framework of Critical Discourse Analysis (CDA) by Norman Fairclough which looks at discourse at the level of textual features, discursive practice and social practice. The data comprises selected utterances from the podcast episode that directly address masculinity, aggression, institutional culture, censorship and freedom of expression. Data were collected by purposive sampling and thematically analyzed based on research objectives. The findings reveal that masculinity is discursively constructed as a natural, positive, and socially valuable identity associated with strength, competitiveness, resilience, authenticity, and independence. The discourse frequently positions masculine traits as being constrained by contemporary institutional and corporate cultures, which are represented as excessively restrictive, politically regulated, and detached from authentic social values. Furthermore, anti-establishment discourse functions as a key ideological mechanism through which masculine identity is legitimized and defended. Institutions, including corporate environments and systems of content regulation, are frequently portrayed as limiting individual freedom and suppressing authentic expression. The podcast setting itself contributes to this construction by fostering an atmosphere of spontaneity, intimacy, and perceived authenticity that strengthens audience engagement with anti-establishment narratives. By showing how long-form conversational media are crucial venues for negotiating masculine identities and institutional power in modern digital culture, this study adds to the expanding corpus of research on digital masculinity, podcast discourse, and alternative media.